Assessing value-in-use: A conceptual framework and exploratory study - Macdonald, Emma K.; Wilson, Hugh; Martinez, Veronica; Toossi, Amir (Elsevier Science B.V., Amsterdam., 2011)
Developing approaches for understanding customer perceived value is a priority for managers and scholars alike. A conceptual framework for assessment of value-in-use is proposed and explored within the context of a maintenance service provider. In contrast to value models in previous empirical research, the framework includes assessment not just of provider attributes but also of the customer's usage processes, as well as customer evaluations of the value-in-use they obtain. Interviews with members of a cross-disciplinary buying group provide support for the framework, including the observations that individuals can assess the quality of their usage processes and that they can articulate value-in-use at both organizational and individual levels; the further concept of network quality also emerges from the data. Assessment of usage process quality as well as service quality evolves as the customer's goals evolve. Practitioners may wish to elicit usage process quality and value-in-use as well as service quality. Research directions include scale development for both usage process quality and value-in-use.
Keywords: Value-in-use; customer perceived value; service quality; usage process; service-dominant logic